Congenital four-limb Lymphedema: a case report - Mansoor, Mahym; Wajieha Saeed; Ghazala Butt; Faria Altaf; Ijaz Hussain (Journal of Pakistan Association of Dermatologists, 2023)
Primary lymphedema is a rare genetic, progressive disorder characterized by swelling due to inadequate lymphatic drainage by defective lymphatic vessels. Here we report a case of a teenage girl presenting with primary lymphedema but with erratic family history and features supportive of both a dominant and recessively inherited described mutations